Differentiated Spelling Instruction and the Impact on Student Spelling - Schlosser, Jacquelyn M. (My University, 2017)
How does my students’ spelling proficiency change after I utilize differentiated spelling and word work? This study looks at the effects using differentiated spelling instruction has on 13 students’ spelling. Students took the Words Their Way (Bear, Invernizzi,Templeton, & Johnston, 2016) Qualitative Spelling Inventory at the beginning and end of the study. My research showed most students improved their spelling with the use of differentiation, while others showed no improvement or regression.
Keywords: elementary; reading; spelling; differentiation